Epidemiological pattern and outcome of head injuries during festive and non-festive periods in a tertiary hospital, Nnewi, Nigeria - Adogu, Prosper O. U.; Egenti, Nonye B.; Ubajaka, Chika F.; Anakwue, Jude C.; Ugezu, Anthony I. (International Journal of Research in Medical Sciences, 2017)
Background: Head injury is trauma to the brain and/or its coverings as a result of an externally applied mechanical force. Study of epidemiological pattern of head injuries is essential in developing necessary preventive strategies and control. To compare the prevalence and pattern of head injuries during the non-festive (February – September) and the festive (October – January) periods in our environment. Methods: Patients’ case files at the Accidents and Emergency unit of Nnamdi Azikiwe University Teaching Hospital (NAUTH), Nnewi, were reviewed. Results: Two hundred and sixty-six out of 4,846 met the inclusion criteria for traumatic head injury and were recruited for the study, giving a prevalence of 5.5%. About 77.4% of these presentations were males while 22.6% were females. Both males and females were affected more in the festive period (52.4% and 48.3%) than in the non-festive period (51.7% and 47.6%). The >20 – 30 year group recorded the highest presentation at 30.5%. Traders and Commercial Motorcyclists were the most affected occupations with 25.9% and 24.1% respectively, with the most common causes of head injury during both the festive and non – periods being motorcycle and motor vehicle accidents (68% and 18% respectively). About 63% presented with mild head injury, 14% with moderate and 23% with severe head injuries. About 11.4% were discharged, 83.9% were transferred to the ward for further evaluation and monitoring while 4.7% died at the Accident and Emergency department. Conclusions: Traumatic head injury is one of the major causes of mortality and morbidity in our environment especially in the festive periods. Aggressive and sustained traffic safety education is recommended for all stakeholders in the broad field of accidentology.